Estimating the effects of human capital constraints on innovation in the Caribbean - Jeetendra Khadan (Economies, 2018)
Human capital, as reflected in education levels and skills, and innovation is an important engine of economic growth. The Caribbean is deficient in both: lower than expected GDP growth rates are accompanied by relatively low innovation at the firm level, and the workforce is characterised by skills deficiencies and educational mismatches. In that regard, this paper exploits firm-level data covering 13 Caribbean countries to examine the extent to which innovation, a key driver of productivity growth, is affected by firms' inability to find appropriately educated and skilled workers to fill key positions in its organizational structure, which is estimated using Probit models distinguishing between past and future innovation decisions. The econometric analysis finds that firms that have difficulty finding new skilled employees are less likely to engage in any type of innovation compared to those that can, and this is also true for decisions about future technological and non-technological innovations. Moreover, firms that face challenges finding employees with the required core and job-related skills at the managerial and professional levels are also less likely to innovate. Finally, while in-firm training is found to increase the probability of innovation, its magnitude is low.
Keywords: C01; D22; J24; 330; educational mismatches; skills and training; innovation; Caribbean